Program Golansia pada Pengembangan Psikoedukasi Keluarga dalam Meningkatkan Latagis (Lansia Tangguh Psikologis) di Wilayah Kerja Ranting Aisyiyah Patrang Jember - Susi Wahyuning Asih; Dian Ratna Elmaghfuroh; Wulan Maulida; Fatimatus Zahro (Jurnal Pengabdian Teknologi Informasi dan Kesehatan, 2023)
Increasing health problems both physical and psychological in elderly partners are of particular concern. Partners' health problems include the increased risk of psychological health problems and the absence of an activity program to maintain the psychological health of the elderly. The Golansia Program in Family Psychoeducation is an elderly health approach program in psychological health education that was developed to increase the mental health strength of the elderly. The Golansia program was developed following the Unmuh Jember community service strategic plan and government policies regarding elderly health care. This program collaborates with the Head of the Aisyiyah Patrang Branch in the field of Elderly Health in the Patrang Village, Patrang District, Jember. The methods that will be used to achieve these goals are 1) education; 2) family psychoeducation practice; and 3) family psychoeducation assistance for the elderly and families through Aisyiyah recitation or health councils with an evaluation of the processes and results of the Golansia Program activities for the elderly to improve Latagis with the Family. The results of this activity obtained an increase in good knowledge of 47.1%. The output of this activity is that it is hoped that there will be continuity for families who provide psychoeducation to the elderly so that psychologically resilient elderly people are formed in the Working Area of the Aisyiyah Patrang Branch, Jember Regency.